KORELASI OPTIMASI PRODUKSI UNTUK SHALE GAS RESERVOIR DENGAN MULTIPLE TRANSVERSE HYDRAULIC FRACTURE - Alfarizi, Ridwan
Shale gas reservoir is one of the unconventional reservoir that is currently being developed in the midst of the hustle and bustle of the energy crisis caused by the conventional reservoir that its production begins to drop and, in the other hand, new reserves is difficult to find. Shale gas reservoir has small permeability and porosity so it was not economical to be produced at the past time. By the development of technology and the demand of natural gas tends to increase, the production of shale gas reservoir has begun to be considered. The technology developed is multiple transverse hydraulic fractures which can produce an optimum production. In this study, the optimization is conducted using the simulator to do sensitivity to the influential parameters. Furthermore, optimization is conducted for optimum gas rate and plateau time against to some of the most influential parameters from sensitivity, and the correlations are generated for predicting optimum gas rate and plateau time. To find out the reservoir performance, IPR is also developed on shale gas reservoir.